Lecture Musicale by Raharimanana: "Les îles témoins et les mémoires tissées" (Readings, Concerts and other events, 2023)
In December 2021, the Africa Multiple Cluster of Excellence hosted a special evening at @kunst-undkulturhausneunein8931: LECTURE MUSICALE with musician and poet Raharimanana. Raharimanana reads, on the notes of his marovany, Malagasy harp, extracts from his books Tisser, (éditions Mémoire d’encrier, 2021), and Le Voi, le Loin, 100 poèmes (editions Vents dailleurs, 2021). Witness-Islands and (en)Tangled Memories. From the movements of the worlds, the islands were formed. Convergence of currents. Utopia of the breaths. Raharimanana is aware of the influx of sources in him. Multiple origins, Africa, Asia, the West. An archipelagic identity where history is sometimes violent, but culture always heals and restores. Poetry, music. Reintegrate the fullness of the world and reconnect with the body. To shiver. To be attentive. Drawing from the myths of the Big Island to write a contemporary fable where the ancestors teach the place of the human, living among the living, "humus of the Earth". Describing the dreams of excess of some and the quest for freedom of others. To live then as fibers to weave humanity.